2012
DOI: 10.1063/1.4723275
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition in BCx system under high-pressure and high-temperature: Synthesis of cubic dense BC3 nanostructured phase

Abstract: Abstract. We synthesized a cubic BC 3 (c-BC 3 ) phase, by direct transformation from graphitic phases at a pressure of 39 GPa and temperature of 2200 K in a laser-heated diamond anvil cell (DAC). A combination of x-ray diffraction (XRD), electron diffraction (ED), transmission electron microscopy (TEM) imaging, and electron energy loss spectroscopy (EELS) measurements lead us to conclude that the obtained phase is hetero-nano-diamond, c-BC 3 . Highresolution TEM (HRTEM) imaging of the c-BC 3 specimen recovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 64 publications
5
58
0
1
Order By: Relevance
“…Several theoretical studies have attempted to propose the crystal structure for C 3 B [9] using intuitive models for distributing of B atoms in graphite-type supercells. The most recent experimental study [10] revealed another diamond-like phase with C 3 B stoichiometry and unknown distribution of C and B atoms at 39 GPa and 2200 K. Theoretical study of Liu et al [11] predicted, using a swarm-optimization algorithm, which was combined with the first-principles structural relaxations, three metallic diamond-based structural arrangements, which had lower energies than all previously considered intuitive models. C 5 B was reported very recently by Solozhenko et al [12] in a course of the laser heating of samples in the diamond-anvil-cell and further quenching them from 24 GPa and ~2200 K to ambient conditions.…”
Section: B Was Reported During Chemical-vapour Deposition (Cvd) Gmentioning
confidence: 99%
“…Several theoretical studies have attempted to propose the crystal structure for C 3 B [9] using intuitive models for distributing of B atoms in graphite-type supercells. The most recent experimental study [10] revealed another diamond-like phase with C 3 B stoichiometry and unknown distribution of C and B atoms at 39 GPa and 2200 K. Theoretical study of Liu et al [11] predicted, using a swarm-optimization algorithm, which was combined with the first-principles structural relaxations, three metallic diamond-based structural arrangements, which had lower energies than all previously considered intuitive models. C 5 B was reported very recently by Solozhenko et al [12] in a course of the laser heating of samples in the diamond-anvil-cell and further quenching them from 24 GPa and ~2200 K to ambient conditions.…”
Section: B Was Reported During Chemical-vapour Deposition (Cvd) Gmentioning
confidence: 99%
“…Син-тез наногетероалмаза в условиях сверхвысоких давлений и температур подтвердил прогноз о том, что введение атомов В в алмаз не должно приводить к значительному искажению его кубической ячейки [2].…”
Section: поступило в редакцию 2 марта 2018 гunclassified
“…They are all found to have outstanding properties such as high elastic modulus and hardness. Recently, considerable efforts have been made to synthesize and predict possible new superhard materials in B-C system, such as BC 2 , BC 3 , BC 5 , and BC 7 [5][6][7][8][9][10][11][12]. For example, diamond-like BC 3 phase has been synthesized from the graphite-like BC 3 phase at 2033 ± 241 K and 50 GPa [10].…”
Section: Introductionmentioning
confidence: 99%